THE EFFECT OF DRAWING AND PRESENTATION ACTIVITY ON EARLY ADOLESCENTS’ HAPPINESS IN ORPHANAGES - Hafnidar Hafnidar; Dina Rahma Lubis; Salsa Meutia; Silvia Putrie Ardana (Yayasan Adra Karima Hubbi, 2025)
This study examines the effect of Drawing and Presentation Activity on the happiness of early adolescents living in an orphanage setting. The research aims to determine whether expressive learning activities that combine visual representation and verbal presentation can enhance adolescents’ subjective well-being. A quantitative experimental approach was employed using a pretest–posttest design with a control group. Participants consisted of early adolescents residing in an orphanage, who were divided into an experimental group receiving the Drawing and Presentation Activity intervention and a control group receiving regular activities. Data were collected using a standardized happiness scale and analyzed using statistical tests to examine differences between groups. The results indicate a significant increase in happiness scores among adolescents who participated in the Drawing and Presentation Activity compared to those in the control group. The novelty of this study lies in integrating creative drawing and structured presentation as an educational activity to promote emotional well-being among marginalized adolescents. Furthermore, this activity-based approach emphasizes active engagement, reflection, and communication, which are essential components in learner-centered pedagogy. The findings imply that creative and participatory learning strategies can be effectively applied not only to support students’ psychological well-being but also to enhance engagement and motivation in educational contexts, including physics and physics education. By fostering positive emotions and self-expression, such activities may indirectly support meaningful learning processes, conceptual understanding, and students’ readiness to engage in science learning.